Amidoxime functionalized nanocellulose porous material as well as preparation method and application thereof

Through cross-linking and polymerization of nanocellulose with nitrile-containing functional group cross-linking agent and amine oximation reaction, nanocellulose porous materials with high specific surface area were prepared, which solved the problem of low adsorption performance of cellulose-based adsorption materials and realized heavy metals The efficient adsorption and recycling of ions have environmentally friendly and economical industrial application potential.

CN119286047APending Publication Date: 2025-01-10ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411484224.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing cellulose-based adsorption materials have low adsorption performance, difficulty in recycling, environmental pollution and insufficient adsorption capacity, making it difficult to efficiently remove heavy metal ions in industrial wastewater.

Method used

Through cross-linking and polymerization of nanocellulose with a small molecule cross-linking agent containing nitrile functional groups, combined with a gastroxime oximation reaction, a functionalized nanocellulose porous material with a multi-stage porous structure and a high specific surface area was prepared. High-efficiency adsorption of heavy metal ions in industrial wastewater.

Benefits of technology

It realizes efficient adsorption and recycling of heavy metal ions, the material regeneration process is simple, low cost, and the preparation process is gentle and safe, and does not require a specific reaction device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286047A_ABST
    Figure CN119286047A_ABST
Patent Text Reader

Abstract

The invention relates to an amidoxime functionalized nanocellulose porous material and a preparation method and application thereof.The preparation method comprises the steps that nanocellulose and a dispersing agent are fully mixed to prepare emulsion, then the emulsion and a cross-linking agent micromolecular monomer containing nitrile functional groups are subjected to cross-linking polymerization through a nucleophilic substitution reaction, and the amidoxime functionalized nanocellulose porous material is obtained. And then carrying out amidoximation reaction on nitrile functional groups contained in the cross-linked polymer to prepare the amidoxime functionalized nano-cellulose porous material. The preparation method is simple, and reaction conditions are mild; the obtained amidoxime functionalized nanocellulose porous material has a hierarchical pore structure, a relatively high specific surface area and various active binding sites, and can be used for efficiently removing heavy metal ions in industrial wastewater; and the amidoxime functionalized nano cellulose porous material can be simply recycled, and the amidoxime functionalized nano cellulose porous material can still keep a relatively high adsorption effect after 20 times of cyclic adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical technology, further to the field of functional cellulose nanomaterials, and in particular to a method for preparing a nano-cellulose-based nanoporous adsorption material. Background Art

[0002] As a typical biomass-based material, cellulose has the advantages of low price, environmental friendliness, high mechanical strength, and seawater corrosion resistance. It contains abundant hydroxyl groups on the surface, has strong hydrophilicity and is easy to modify. In addition, the hydrophilicity of cellulose can accelerate the diffusion of pollutants in wastewater into the interior of the adsorbent, which is conducive to adsorption. And when cellulose is used as the main adsorption material, the amount of synthetic polymer will be reduced accordingly, thereby reducing costs. The defect is that the adsorption performance of the cellulose material itself is low, and it needs to be modified by various chemical methods to improve its adsorption performance and selectivity. The design and preparation of cellulose-based adsorbents with high adsorption capacity, high selectivity, excellent anti-fouling performance and large-scale industrial application are hot research directions. The amidoxime group has excellent binding ability for heavy metal ions, but the existing amidoxime adsorbent materials often have poor hydrophilicity, complex preparation process, high-energy radiation grafting, radiation damage to the material, difficulty in recycling the material, pollution to the environment, low adsorption capacity, and difficulty in desorption and regeneration.

[0003] Therefore, those skilled in the art are in urgent need of providing a nanocellulose porous material with good adsorption properties, multiple recycling capabilities, and good regeneration performance. Summary of the invention

[0004] The present invention aims to overcome at least one of the shortcomings and deficiencies of the above-mentioned prior art, provide an amidoxime functionalized nanocellulose porous material and a preparation method and application thereof, synthesize an adsorption material with a large specific surface area and a variety of active functional group binding sites, and realize efficient adsorption of heavy metal ions in industrial wastewater. The purpose of the present invention is achieved based on the following technical solutions:

[0005] The first aspect of the present invention provides a method for preparing an amidoxime functionalized nanocellulose porous material, wherein nanocellulose and a small molecule cross-linking agent containing a nitrile functional group are subjected to a cross-linking polymerization reaction, followed by an amidoximation reaction to prepare the amidoxime functionalized nanocellulose porous material.

[0006] Preferably, the preparation method specifically comprises the following steps:

[0007] S1. Under normal temperature conditions, a certain amount of nanocellulose is fully dispersed in a certain volume of dispersant to prepare a uniform and stable nanocellulose dispersion, and then a certain amount of catalyst is placed in the dispersion, stirred until fully mixed, a certain amount of cross-linking agent is placed in the above mixed solution, the reaction temperature is adjusted, and mechanical stirring is performed for a certain period of time to perform an in-situ cross-linking polymerization reaction;

[0008] S2, after the reaction of step S1 is completed, the cross-linked polymer obtained by the reaction of S1 is subjected to amidoximation reaction by hydroxylamine hydrochloride;

[0009] S3. After the reaction of step S2 is completed, the solid product is repeatedly washed with an ethanol solution, and then the solid product is placed in deionized water and dialyzed for 24 to 72 hours. The obtained product is then freeze-dried to obtain an amidoxime functionalized nanocellulose porous material with controllable microstructure.

[0010] Preferably, in step S1: the dispersant comprises one of N, N-dimethylformamide, dimethyl sulfoxide or tetrahydrofuran;

[0011] The catalyst includes one of cesium carbonate, potassium carbonate or sodium carbonate;

[0012] The cross-linking agent includes one or more of tetrafluoroterephthalonitrile, tetrafluorophthalonitrile, tetrachloroterephthalonitrile and tetrachlorophthalonitrile.

[0013] Preferably, in step S1, the weight ratio of nanocellulose to catalyst is 3:1 to 1:3, and the weight ratio of nanocellulose to cross-linking agent is 3:1 to 1:3.

[0014] Preferably, the stirring speed of the cross-linking polymerization reaction in step S1 is 500-1500 rpm, the reaction temperature is 60-80° C., and the reaction time is 6-12 h.

[0015] Preferably, in the amidoximation reaction in step S2, the weight feed ratio of hydroxylamine hydrochloride to nanocellulose is 2:1 to 1:2, the reaction temperature is 60 to 80° C., and the reaction time is 6 to 12 h.

[0016] Preferably, the freeze-drying temperature in step S3 is -90 to -30°C, and the drying time is 24 to 72 hours.

[0017] The second aspect of the present invention provides an amidoxime functionalized nanocellulose porous material, which is prepared according to the above preparation method.

[0018] The third aspect of the present invention provides an application of amidoxime functionalized nanocellulose porous material in adsorbing heavy metal ions in industrial wastewater.

[0019] Among the professional terms, NC refers to nanocellulose, DMF refers to N, N-dimethylformamide, DMSO refers to dimethyl sulfoxide, and THF refers to tetrahydrofuran.

[0020] The present invention can achieve at least one of the following beneficial effects:

[0021] 1. The present invention uses nanocellulose (NC) and a small molecule crosslinking agent containing a nitrile functional group as raw materials to prepare a nanocellulose crosslinked polymer through a crosslinking polymerization reaction. Compared with existing cellulose-based porous materials, the amidoxime functionalized nanocellulose porous material prepared by the present invention not only has a multi-level pore structure and a high specific surface area, but also has a variety of active functional group binding sites, which can be used for the efficient adsorption and removal of heavy metal ions in industrial wastewater.

[0022] 2. The amidoxime functionalized nanocellulose porous material obtained by the present invention can be recycled and used to adsorb and remove heavy metal ions in wastewater. After 20 cycles of adsorption, it can still maintain a high adsorption effect. The regeneration process of the adsorption material is simple and the recycling cost is low.

[0023] 3. The preparation method of the amidoxime functionalized nanocellulose porous material of the present invention is simple, the reaction conditions are mild and not harsh, the process is safe, and no specific reaction device is required. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the reaction process of amidoxime functionalized nanocellulose porous materials.

[0025] Figure 2 These are indicator diagrams of various embodiments of amidoxime functionalized nanocellulose porous materials. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] A method for preparing amidoxime functionalized nanocellulose porous material comprises carrying out crosslinking polymerization reaction on nanocellulose and a small molecule crosslinking agent containing a nitrile functional group, and then carrying out amidoximation reaction to prepare the amidoxime functionalized nanocellulose porous material.

[0028] The preparation method specifically comprises the following steps:

[0029] S1. Under normal temperature conditions, a certain amount of nanocellulose is fully dispersed in a certain volume of dispersant to prepare a uniform and stable nanocellulose dispersion, and then a certain amount of catalyst is placed in the dispersion, stirred until fully mixed, a certain amount of cross-linking agent is placed in the above mixed solution, the reaction temperature is adjusted, and mechanical stirring is performed for a certain period of time to perform an in-situ cross-linking polymerization reaction;

[0030] S2, after the reaction of step S1 is completed, the cross-linked polymer obtained by the reaction of S1 is subjected to amidoximation reaction by hydroxylamine hydrochloride;

[0031] S3. After the reaction of step S2 is completed, the solid product is repeatedly washed with an ethanol solution, and then the solid product is placed in deionized water and dialyzed for 24 to 72 hours. The obtained product is then freeze-dried to obtain an amidoxime functionalized nanocellulose porous material with controllable microstructure.

[0032] In step S1: the dispersant includes one of N, N-dimethylformamide, dimethyl sulfoxide or tetrahydrofuran;

[0033] The catalyst includes one of cesium carbonate, potassium carbonate or sodium carbonate;

[0034] The crosslinking agent includes one or more of tetrafluoroterephthalonitrile, tetrafluorophthalonitrile, tetrachloroterephthalonitrile and tetrachlorophthalonitrile.

[0035] In step S1, the weight ratio of nanocellulose to catalyst is 3:1 to 1:3, and the weight ratio of nanocellulose to cross-linking agent is 3:1 to 1:3.

[0036] In step S1, the stirring speed of the cross-linking polymerization reaction is 500-1500 rpm, the reaction temperature is 60-80° C., and the reaction time is 6-12 h.

[0037] In step S2, the weight ratio of hydroxylamine hydrochloride to nanocellulose in the amidoximation reaction is 2:1 to 1:2, the reaction temperature is 60 to 80° C., and the reaction time is 6 to 12 hours.

[0038] The freeze-drying temperature in step S3 is -90 to -30°C, and the drying time is 24 to 72 hours.

[0039] The present invention also provides an amidoxime functionalized nano-cellulose porous material, which is prepared according to the above preparation method.

[0040] The invention also provides an application of amidoxime functionalized nano-cellulose porous material in adsorbing heavy metal ions in industrial wastewater.

[0041] Among the professional terms, NC refers to nanocellulose, DMF refers to N, N-dimethylformamide, DMSO refers to dimethyl sulfoxide, and THF refers to tetrahydrofuran.

[0042] The molecular structure and composition of the amidoxime functionalized nanocellulose porous material finally synthesized by the present invention are tested and analyzed by nuclear magnetic resonance (13CNMR, 1HNMR) and Fourier transform infrared spectrometer (FTIR); the specific surface area, porosity, pore size and distribution range of the amidoxime functionalized nanocellulose porous material are analyzed by BET test.

[0043] The adsorption effect of amidoxime functionalized nanocellulose porous materials on heavy metal ions in wastewater was analyzed by atomic energy spectrometry (ICP) test. The specific test method is as follows: prepare a Cu2+ solution with a mass concentration of 100-1000 mg / L, take 20 mg of amidoxime functionalized nanocellulose porous material, and place it in 20 ml of heavy metal ion solution with different concentrations, respectively. At room temperature and pH = 5, stir and adsorb in a water bath shaker for 12 hours, and use an atomic energy spectrometer to determine the Cu2+ concentration in the solution before and after adsorption.

[0044] The specific recycling process of amidoxime functionalized nanocellulose porous material is as follows: the adsorbent material saturated with heavy metal ions is placed in an acidic methanol or ethanol solution and soaked for 10 minutes, then filtered using a circulating water pump and a Buchner funnel, the solid is collected, and freeze-dried at -60°C for 48 hours, and the obtained solid material is used for the cyclic adsorption of heavy metal ions.

[0045] The specific embodiments are as follows:

[0046] Example 1

[0047] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0048] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Potassium carbonate (5 g) and tetrafluoroterephthalonitrile (5 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to potassium carbonate was 1:1, and the weight ratio of nanocellulose to tetrafluoroterephthalonitrile was 1:1.

[0049] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (5 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 6 h, the stirring speed is 600 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 1:1.

[0050] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialyzed for 48 hours. The obtained product is then freeze-dried at -80°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0051] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=197.18 m2 / g and a porosity of up to 89.6%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 95.2%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 83.3%.

[0052] Example 2

[0053] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0054] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 500 rpm. Potassium carbonate (10 g) and tetrafluoroterephthalonitrile (10 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 80°C, the reaction time was 48 hours, the stirring speed was 500 rpm, the weight ratio of nanocellulose to potassium carbonate was 1:2, and the weight ratio of nanocellulose to tetrafluoroterephthalonitrile was 1:2.

[0055] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 6 h, the stirring speed is 500 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0056] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water. The water is changed every 2 hours and dialyzed for 24 hours. The obtained product is then freeze-dried at -40°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0057] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=215.53 m2 / g and a porosity of up to 91.6%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 99.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 98.3%.

[0058] Example 3

[0059] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0060] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 1000 rpm. Then, sodium carbonate (10 g) and tetrafluorophthalonitrile (5 g) were added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 60°C, the reaction time was 36 hours, the stirring speed was 1000 rpm, the weight ratio of nanocellulose to sodium carbonate was 1:2, and the weight ratio of nanocellulose to tetrafluorophthalonitrile was 1:1.

[0061] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 6 h, the stirring speed is 500 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0062] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 36 hours. The obtained product is then freeze-dried at -50°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0063] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=205.51 m2 / g and a porosity of up to 90.9%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 99.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 97.9%.

[0064] Example 4

[0065] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0066] (1) 200 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 1000 rpm. Potassium carbonate (15 g) and tetrafluorophthalonitrile (10 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 48 hours, the stirring speed was 1000 rpm, the weight ratio of nanocellulose to potassium carbonate was 1:3, and the weight ratio of nanocellulose to tetrafluorophthalonitrile was 1:2.

[0067] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (5 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 12 h, the stirring speed is 1000 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 1:1.

[0068] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 36 hours. The obtained product is then freeze-dried at -80°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0069] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=212.58 m2 / g and a porosity of up to 93.1%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 99.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 97.1%.

[0070] Example 5

[0071] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0072] (1) 200 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Potassium carbonate (15 g) and tetrachloroterephthalonitrile (15 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 80°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to potassium carbonate was 1:3, and the weight ratio of nanocellulose to tetrachloroterephthalonitrile was 1:3.

[0073] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 12 h, the stirring speed is 600 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0074] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 36 hours. The obtained product is then freeze-dried at -70°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0075] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=201.12 m2 / g and a porosity of up to 88.9%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 98.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 96.1%.

[0076] Example 6

[0077] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0078] (1) 180 ml of N,N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Then, cesium carbonate (2.5 g) and tetrachloroterephthalonitrile (2.5 g) were added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 80°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to cesium carbonate was 2:1, and the weight ratio of nanocellulose to tetrachloroterephthalonitrile was 2:1.

[0079] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 6 h, the stirring speed is 500 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0080] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 24 hours. The obtained product is then freeze-dried at -80°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0081] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=196.72 m2 / g and a porosity of up to 90.1%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 96.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 93.3%.

[0082] Example 7

[0083] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0084] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 12 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Then, cesium carbonate (12 g) and tetrachloroterephthalonitrile (3.0 g) were added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to cesium carbonate was 1:2, and the weight ratio of nanocellulose to tetrachloroterephthalonitrile was 1:2.

[0085] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (2.5 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 6 h, the stirring speed is 600 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 1:2.

[0086] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 48 hours. The obtained product is then freeze-dried at -80°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0087] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=185.69 m2 / g and a porosity of up to 86.9%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 96.8%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 91.5%.

[0088] Example 8

[0089] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0090] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Potassium carbonate (10 g) and tetrafluoroterephthalonitrile (10 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to potassium carbonate was 1:2, and the weight ratio of nanocellulose to tetrafluoroterephthalonitrile was 1:1.

[0091] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 12 h, the stirring speed is 600 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0092] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 24 hours. The obtained product is then freeze-dried at -80°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0093] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=176.53 m2 / g and a porosity of up to 84.7%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 95.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 90.1%.

[0094] Example 9

[0095] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0096] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 6 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 1000 rpm. Potassium carbonate (2 g) and tetrachlorophthalonitrile (3.0 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 24 hours, the stirring speed was 1000 rpm, the weight ratio of nanocellulose to potassium carbonate was 3:1, and the weight ratio of nanocellulose to tetrachlorophthalonitrile was 2:1.

[0097] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (12 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 12 h, the stirring speed is 1000 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0098] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 24 hours. The obtained product is then freeze-dried at -60°C for 36 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0099] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=172.68 m2 / g and a porosity of up to 84.1%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 95.6%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 90.6%.

[0100] Example 10

[0101] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0102] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 6 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 1000 rpm. Then, sodium carbonate (3 g) and tetrafluoroterephthalonitrile (2.0 g) were added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 70°C, the reaction time was 24 hours, the stirring speed was 1000 rpm, the weight ratio of nanocellulose to sodium carbonate was 2:1, and the weight ratio of nanocellulose to tetrafluoroterephthalonitrile was 3:1.

[0103] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (6 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 70° C., the reaction time is 12 h, the stirring speed is 1000 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 1:1.

[0104] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialyzed for 48 hours. The obtained product is then freeze-dried at -70°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0105] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=171.21 m2 / g and a porosity of up to 83.1%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 94.1%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 89.9%.

[0106] Embodiment 11

[0107] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0108] (1) 180 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 6 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 600 rpm. Potassium carbonate (2 g) and tetrachloroterephthalonitrile (2.0 g) were then added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 80°C, the reaction time was 48 hours, the stirring speed was 600 rpm, the weight ratio of nanocellulose to potassium carbonate was 3:1, and the weight ratio of nanocellulose to tetrachloroterephthalonitrile was 3:1.

[0109] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (12 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 12 h, the stirring speed is 600 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0110] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 24 hours. The obtained product is then freeze-dried at -60°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0111] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=151.67 m2 / g and a porosity of up to 81.8%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 93.3%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 88.6%.

[0112] Example 12

[0113] In this embodiment, the preparation method of amidoxime functionalized nanocellulose porous material comprises the following steps:

[0114] (1) 200 ml of N, N-dimethylformamide (DMF) was placed in a round-bottom flask at room temperature, and then nanocellulose (NC, 5 g) was added to the round-bottom flask and stirred until the nanocellulose was uniformly dispersed for 1 hour at a stirring speed of 1000 rpm. Then, cesium carbonate (15 g) and tetrafluoroterephthalonitrile (5 g) were added to the round-bottom flask and stirred for cross-linking polymerization. The reaction temperature was 80°C, the reaction time was 48 hours, the stirring speed was 1000 rpm, the weight ratio of nanocellulose to cesium carbonate was 1:3, and the weight ratio of nanocellulose to tetrafluoroterephthalonitrile was 1:1.

[0115] (2) After the reaction of step (1) is completed, hydroxylamine hydrochloride (10 g) is added to the above reaction mixture, and amidoximation reaction is carried out by stirring. The reaction temperature is 80° C., the reaction time is 12 h, the stirring speed is 1000 rpm, and the weight ratio of hydroxylamine hydrochloride to nanocellulose is 2:1.

[0116] (3) After the reaction in step (2) is completed, the reaction mixture is filtered, washed repeatedly with 200 ml of ethanol for three times, and then placed in a dialysis bag (US Viskase, MWCO8000 regenerated cellulose dialysis bag), and then placed in 2000 ml of deionized water, the water is changed every 2 hours, and the dialysis is performed for 48 hours. The obtained product is then freeze-dried at -80°C for 48 hours to obtain an amidoxime functionalized nanocellulose porous material.

[0117] The synthesized amidoxime functionalized nanocellulose porous material has a specific surface area SBET=216.91 m2 / g and a porosity of up to 94.6%. The adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 99.9%. After 20 cycles of adsorption, the adsorption rate of the sample for heavy metal ions (Cu2+) is as high as 98.1%.

[0118] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing amidoxime functionalized nanocellulose porous material, characterized in that: The nanocellulose and a small molecule cross-linking agent containing a nitrile functional group are subjected to a cross-linking polymerization reaction, followed by an amidoximation reaction to prepare an amidoxime functionalized nanocellulose porous material.

2. A method for preparing amidoxime functionalized nanocellulose porous material, characterized in that: The specific steps include: S1. Under normal temperature conditions, a certain amount of nanocellulose is fully dispersed in a certain volume of dispersant to prepare a uniform and stable nanocellulose dispersion, and then a certain amount of catalyst is placed in the dispersion, stirred until fully mixed, a certain amount of cross-linking agent is placed in the above mixed solution, the reaction temperature is adjusted, and mechanical stirring is performed for a certain period of time to perform an in-situ cross-linking polymerization reaction; S2, after the reaction of step S1 is completed, the cross-linked polymer obtained by the reaction of S1 is subjected to amidoximation reaction by hydroxylamine hydrochloride; S3. After the reaction of step S2 is completed, the solid product is repeatedly washed with an ethanol solution, and then the solid product is placed in deionized water. After dialysis, the obtained product is freeze-dried to obtain an amidoxime functionalized nanocellulose porous material with controllable microstructure.

3. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 2, characterized in that: In step S1, the dispersant is one or more of N, N-dimethylformamide, dimethyl sulfoxide or tetrahydrofuran; The catalyst is one or more of cesium carbonate, potassium carbonate or sodium carbonate; The cross-linking agent is one or more of tetrafluoroterephthalonitrile, tetrafluorophthalonitrile, tetrachloroterephthalonitrile and tetrachlorophthalonitrile.

4. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 2, characterized in that: In step S1, the weight ratio of the nanocellulose to the catalyst is 3:1 to 1:3, and the weight ratio of the nanocellulose to the cross-linking agent is 3:1 to 1:

3.

5. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 3, characterized in that: In step S1, the in-situ cross-linking polymerization reaction has a stirring speed of 500 to 1500 RPM, a reaction temperature of 60 to 80° C., and a reaction time of 6 to 12 hours.

6. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 3, characterized in that: The amidoximation reaction temperature in step S2 is 60-80° C., and the reaction time is 6-12 h.

7. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 3, characterized in that: In step S3, the dialysis time is 24 to 72 hours.

8. The method for preparing an amidoxime functionalized nanocellulose porous material according to claim 3, characterized in that: In step S3, the freeze-drying temperature is -90 to -30°C, and the drying time is 24 to 72 hours.

9. An amidoxime functionalized nanocellulose porous material, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 8.

10. Application of amidoxime functionalized nanocellulose porous material in the adsorption and removal of heavy metal ions from industrial wastewater.

Citation Information

Cited By

  • Amidoxime-based polymer adsorption material as well as preparation method and application thereof

    CN121159880A